World Health Organization Global Health Sector Strategy on Sexually Transmitted Infections: An Evidence-to-Action Brief for Colombia - Melanie Taylor; Monica Alonso-González; Bertha Gómez; Eline Korenromp; Nathalie Broutet (Federación Colombiana de Obstetricia y Ginecología, 2017)
Curable and incurable sexually transmitted infections (STI) are acquired by hundreds of millions of people worldwide each year. Undiagnosed and untreated STIs cause a range of negative health outcomes including adverse birth outcomes, infertility and other long term sequelae such us cervical cancer. In 2016, the World Health Organization (WHO) launched the Global STI Strategy (2016-2021). The WHO Global STI Strategy's public health approach focuses on three causative organisms of STIs that need immediate action and for which cost-effective interventions exist: (a) Neisseria gonorrhoea as a cause of infertility, a risk factor for coinfection with other STIs and because of increasing bacterial resistance to antibiotic treatment, (b) Treponema pallidum given the contribution of syphilis to adverse birth outcomes including stillbirth and neonatal death and (c) Human papillomavirus due to its link to cervical cancer. The range of actions recommended for countries includes: (a) strengthening surveillance, with program monitoring and progress evaluation, (b) STI prevention, (c) early diagnosis of STIs, (d) patient and partner management, and (e) approaches to reach the most vulnerable populations. This summary describes the WHO Global STI Strategy alongside findings from a STI surveillance workshop held in Colombia in May of 2017. Observations related to the Global STI Strategy and findings from the STI estimation workshop are described here for stakeholders in Colombia to consider as they identify opportunities to improve STI services and surveillance.